2023
DOI: 10.1242/bio.059992
|View full text |Cite
|
Sign up to set email alerts
|

The lymphatic system favours survival of a unique T. brucei population

Henrique Machado,
António Temudo,
Mariana De Niz

Abstract: Trypanosoma brucei colonize and multiply in the blood vasculature, as well as in various organs of the host's body. Lymph nodes have been previously shown to harbour large numbers of parasites, and the lymphatic system has been proposed as a key site that allows T. brucei distribution through, and colonization of the mammalian body. However, visualization of host-pathogen interactions in the lymphatic system has never captured dynamic events with high spatial and temporal resolution throughout infection. In ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…This would allow us to study the effect of environment geometry as one of multiple components governing parasite single and collective behaviour. Several studies have focused on the different behaviour exhibited by T. brucei in anatomical locations of different geometry, both in different compartments of the tsetse fly [40][41][42], and different organs and compartments of the mammalian host [43][44][45]. Specifically, and relevant to our observations in Tryp-Chip, we found that parasite motility is affected both, by parasite density, and tissue geometry [46].…”
Section: Plos Onesupporting
confidence: 67%
“…This would allow us to study the effect of environment geometry as one of multiple components governing parasite single and collective behaviour. Several studies have focused on the different behaviour exhibited by T. brucei in anatomical locations of different geometry, both in different compartments of the tsetse fly [40][41][42], and different organs and compartments of the mammalian host [43][44][45]. Specifically, and relevant to our observations in Tryp-Chip, we found that parasite motility is affected both, by parasite density, and tissue geometry [46].…”
Section: Plos Onesupporting
confidence: 67%
“…For T. brucei, the intestinal lumen presents the most obvious point of entry into the faeces. T. brucei has previously been recorded in extravascular lymphoid and adipose tissue surrounding the gastrointestinal tract (GIT) in mice 37,38 , and in peritoneal fluid of infected sheep 40 -however, there was no evidence of extravascular T. congolense in similar infection studies in rats 41 . To what extent T. brucei invades GIT mucosal or epithelial tissue, or sequesters in gut-associated lymphoid tissue within the intestines, is not certain.…”
Section: Discussionmentioning
confidence: 95%
“…GIT pathology findings in T. b. brucei experimentally-infected mice have included villus atrophy and oedema of the lamina propria as a result of inflammation 34,35 . Although extravascular T. brucei parasites have been found in the peritoneal fluid of experimentally-infected cattle 36 and the adipose tissue and lymph nodes surrounding the mesentery of infected mice 37,38 , T. brucei has not been recorded in the GIT mucosa or lumen. In contrast, we are not aware of any evidence of T. congolense in these locations.…”
Section: Take Down Policymentioning
confidence: 99%